1982
DOI: 10.1128/aem.43.4.753-756.1982
|View full text |Cite
|
Sign up to set email alerts
|

Phytate hydrolysis by germfree and conventional rats

Abstract: Phytic acid is a naturally occurring compound that reduces intestinal absorption of many metals. Early work suggests that some dietary phytate may be hydrolyzed in the large intestines by bacteria, but more recently nutritionists have suggested that a mucosal enzyme is responsible. This paper reports a study intended to resolve this controversy. The hydrolysis of dietary phytic acid was measured in germfree and conventional rats fed either of two diets that differed in their calcium content. Negligible phytate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 15 publications
5
29
0
Order By: Relevance
“…As the phytate degradation in the stomach and small intestine was almost unaffected, different supplementation of calcium carbonate predominantly affected the hydrolysis of phytate in the large intestine. Similar results were reported for rats by Pileggi et al [182] and Wise and Gilbert [180]. Most probably, high dietary calcium content affects the phytate solubility in the gastro-intestinal chyme and thereby reduces the accessibility of phytate for enzymatic hydrolysis.…”
Section: Faecessupporting
confidence: 84%
See 1 more Smart Citation
“…As the phytate degradation in the stomach and small intestine was almost unaffected, different supplementation of calcium carbonate predominantly affected the hydrolysis of phytate in the large intestine. Similar results were reported for rats by Pileggi et al [182] and Wise and Gilbert [180]. Most probably, high dietary calcium content affects the phytate solubility in the gastro-intestinal chyme and thereby reduces the accessibility of phytate for enzymatic hydrolysis.…”
Section: Faecessupporting
confidence: 84%
“…Experiments in rats also focussing on phytate hydrolysis in the large intestine [180] reported 56% of phytate hydrolysed in conventional rats while in germfree rats almost no phytate hydrolysis was detected. This finding also emphasises the significance of microbial phytases for phytate degradation during the digestion in the gut and may explain the strong phytate hydrolysis in the large intestine.…”
Section: Large Intestinesupporting
confidence: 84%
“…This might be explained by the detection method, as the presence of high concentrations of anions (including ATP) in the tissue extracts might compromise inositol phosphate separation protocols characterized in their absence (Shears, 2001;Letcher et al, 2008). Furthermore, the results from Wise and Gilburt (1982), who found no significant InsP 6 absorption in the absence of microbial hydrolysing activity, strengthens the suggestion of Letcher et al (2008). Vucenik and Shamsuddin (2006) suggested that the great number of studies showing anticancer activities suggest that InsP 6 or InsP 6 -degradation products have to be absorbed to a certain extent, even though the absorption mechanism still remains to be clarified (Schlemmer et al, 2009).…”
Section: Absorption Of Phytatementioning
confidence: 99%
“…Apparently, phytate, enzyme, protein, and/or substrate complexes that affect digestion in vitro are either broken or not formed in vivo, possibly due to presence of cations or pH changes affecting phytate and/or complex solubility (Cheryan, 1980;Reddy et al, 1982). Additional factors that may influence in vivo effects are mucosal enzymes, bacterial fermentation and/or proteases not inhibited by phytate or its esters (Wise and Gilburt, 1982;Bitar and Reinhold, 1972). Animals consuming the myo-inositol phosphate esters appeared healthy under visual inspection both internally and externally.…”
Section: In Viva Studiesmentioning
confidence: 99%